Accuracy of Patient-Specific Osteosynthesis in Bimaxillary Surgery: Comparative Feasibility Analysis of Four- and Two-Miniplate Fixation - van der Wel, Hylke; Glas, Haye; Jansma, Johan; Schepers, Rutger (Journal of personalized medicine, 2025)
Background/Objectives: Patient-specific osteosynthesis (PSO) plates, in combination with virtual surgical planning (VSP), have significantly improved the accuracy of orthognathic surgery. This study aimed to compare the surgical accuracy of two-plate versus four-plate fixation methods in Le Fort I osteotomies using PSO. Methods: A retrospective cohort study was conducted on 21 patients who underwent maxilla-first bimaxillary surgery at a single centre in 2024. Eight patients received two-plate fixation, while thirteen received four-plate fixation. All surgeries were planned using VSP. Postoperative cone beam computed tomography scans were used to assess the accuracy of maxillary positioning by comparing the planned versus achieved outcomes in terms of translation and rotation. Results: Both fixation methods yielded comparable results in maxillary positioning, with no significant differences observed between the two groups regarding translational or rotational deviations. The two-plate PSO approach demonstrated practical benefits, including reduced material usage and the potential for smaller surgical incisions, without compromising surgical accuracy. Conclusions: Two-plate PSO fixation is a viable alternative to the traditional four-plate method for Le Fort I osteotomies, offering similar accuracy with potential procedural advantages. While these findings support broader clinical adoption, further research is warranted to confirm the results in larger cohorts and to investigate biomechanical considerations.